Le fratture del capitello radiale in età infantile - De Pellegrin, M.; Marcucci, L.; Rosenlechner, T.; Fracassetti, D. (Lo Scalpello - Journal, 2018)
RADIAL NECK FRACTURES IN CHILDRENFractures of the radial neck are rare and account for approximately one percent of all bone fractures in childhood,while severe displaced fractures account for only 1/3 of those. According to the literature, the main complications ofsurgical treatment include loss of function and avascular necrosis. The aim of the study was to describe ourmini-invasive technique and to compare it to eighteen minimally-invasive techniques found after a literature review.Between 1990 and 2017 twelve patients (7 males and 5 females) aged between one and thirteen years (average age 8.3years) with severe displaced radial neck fractures (6 type III, 4 type IVa and 2 type IVb according to Judet’sclassification) were treated with a minimally-invasive technique combining percutaneous Kirschner wire reductionand intramedullary fixation according to Métaizeau. The Metaizeau radiological and functional score evaluation andthe functional score of Tibone and Stoltz were considered. The postoperative x-ray evaluation according to Metaizeaushowed eleven excellent results and one good result. After an average follow-up of 28 months (range 8–110 months)the scores according to Tibone and Stoltz showed 10 excellent results and two good results; the functional evaluationaccording to Métaizeau showed 11 excellent results and one good result. Percutaneous reduction of the displacedradial head in radial neck fracture using a Kirschner wire combined with an intramedullary fixation according toMetaizeau has proven to be simple, effective and without complications.